Integrated transcriptomic and proteomic analysis reveals isolation and culture associated molecular changes in neonatal porcine pancreatic cell clusters - Chang-Yi Chen; Chen-Ling Chen; Chen-Wei Kao; Chen-Yi Chen; Wan-Wen Hung; Ching-Wen Chang; Jyuhn-Huarng Juang; Wan-Chun Li (Molecular Biology Reports, 2026)
Background While porcine Neonatal Pancreatic Cell Clusters (NPCCs) were potential alternative source of islets, their immaturity and heterogeneity make them inefficiently ameliorate hyperglycemia in rodents. Our previous work showed that NPCCs regress to a transitional-like state immediately after isolation and undergo dynamic transcriptional changes during short-term in vitro culture. The present study aimed to further delineate the molecular cues underlying these changes during porcine pancreatic tissue isolation and cultivation. Method Transcriptomic and proteomic analysis were performed to compare Neonatal Porcine Pancreata (NPP), freshly isolated NPCCs (NPCCs-0D) and 3-day in vitro cultured NPCCs (NPCCs-3D). Using an in-house analysis pipeline, molecular differences between groups were identified. Results NPCCs‑0D showed lower molecular abundance compared with NPP and NPCCs‑3D groups under the tested conditions. Gene Sets Enrichment Analysis (GSEA) revealed that pathways related to receptor signaling and cell–microenvironment interactions were enriched in NPP and NPCCs‑3D, highlighting the importance of external regulation in maintaining pancreatic tissue architecture. In contrast. organelle- and catalysis-associated gene sets were enriched in NPCCs‑0D, suggesting a transcriptionally active and adaptive state. Conclusion Collectively, these findings indicate that molecular differences among NPP, NPCCs-0D, and NPCCs-3D reflect changes in tissue organization, cellular composition, and adaptation to isolation and culture conditions, rather than a linear differentiation process.

Modular memristor circuits for Pavlov associative memory with scalability - Xiaoyuan Wang; Zhenyu Ge; Mingyang Wu; Xinrui Zhang; Zhonghai Zhang; Xiaolu Lucia Li; Herbert Ho-Ching Iu; Sung-Mo Kang (Cognitive Neurodynamics, 2026)

Metabolic and growth responses of rainbow trout (Oncorhynchus mykiss) to black soldier fly meal: A meta-analysis and multivariate evaluation of physiological trade-offs - KhaiHang Choong; ZeXin Li; Fui Fui Ching; Leong Seng Lim; Zhou Wu; Karsoon Tan (Aquaculture, 2026)

Subtropical climate and intraday temperature variability: Mental health risks and modifying roles of demographic and seasonal factors in Texas - Yue Zhang; Kaili Zhang; Yizhen Ding; Chia-Ching Wu; Dongying Li (Sustainable Cities and Society, 2026)

Nonlinear structural reorganisation of corn starch induced by high-pressure processing regulates its thermal, pasting and hydration behaviour - Wen-Chien Lu; Yung-Jia Chan; Ching-Jung Lin; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Mechanical anisotropy in pectin films - Joseph Robert Nastasi; Kit Ching Tam; Thu An Le; Chenghao Li; Vassilis Kontogiorgos (Carbohydrate Polymers, 2026)

Real-world onboard evaluation of exhaust aftertreatment effects on particle-bound persistent free radicals and reactive oxygen species generation potential from inland vessels - Yu-Chieh Wang; Wei-Min Ching; Hsi-Hsien Yang; Yen-Hsien Li; Tzu-Hsien Tseng; Hsin-Te Yu (Environmental Pollution, 2026)

ENSO-modulated upstream rainout and convection predominantly control precipitation oxygen isotopes recorded in tree rings from Taiwan’s cloud forests - Nguyen-Xuan Hau; Masaki Sano; Takeshi Nakatsuka; Kevin J. Anchukaitis; Thanh Ngo-Duc; Ying-Shuo Chang; Zhen Li; Le-Thi Thuong; I.-Ching Chen (Climate Dynamics, 2026)

Association of neurofilament light chain, CXCL9, IL-6, and TNFRSF11B with intrinsic capacity in community-dwelling older adults - Reshma Aziz Merchant; Yang Liu; Benjamin Y. Q. Tan; Ching-Hui Sia; Andrea Wong; Li Feng Tan; Gustavo Duque; Hidenori Arai; Bruno Vellas; Jean Woo (GeroScience, 2026)

Circular economy and financial risk in cement manufacturing: A path toward SDG 7 - Xuelian Li; Yujie Cai; Ching-Hui Chang; Jyh-Horng Lin (Journal of Environmental Management, 2026)

Restaurant wastewater as a sustainable medium for ureolytic bacteria in biocementation - Armstrong Ighodalo Omoregie; Thangaraj Pramila; Adharsh Rajasekar; Ching Yi Hong; Hazlami Fikri Basri; Aaron Chew Wei-Li; Chih Siong Wong; Diana Jumbo-Flores (World Journal of Microbiology and Biotechnology, 2026)
Restaurant wastewater (RWW) represents an abundant yet largely unexplored nutrient source for enriching ureolytic microbial consortia applicable to microbial-induced calcite precipitation (MICP). This study characterised RWW collected from a food-service establishment in Johor, Malaysia (COD 1,341 mg/L; BOD 837 mg/L; pH 6.8), and systematically evaluated its capacity to support indigenous ureolytic bacterial enrichment across three media formulations: yeast extract-based (Medium-1), nutrient broth-based (Medium-2), and brown sugar-based (Medium-3). Medium-1 delivered the strongest performance, achieving OD 600 = 1.29 ± 0.06, urease activity = 17.42 ± 1.19 mM urea hydrolysed min − 1 , and CaCO 3 precipitation = 2.81 ± 0.17 g/L. Optimal bioactivity was recorded at pH 8 and 30 °C, conditions closely aligned with the tropical collection environment. 16 S rRNA amplicon sequencing (DADA2 pipeline; SILVA nr v138.1) yielded 101,869 quality-filtered reads across 116 amplicon sequence variants (ASVs; Shannon H = 2.79), identifying a co-dominant community of Firmicutes (50.83%) and Proteobacteria (48.36%), with Sporosarcina (6.09%), Bacillus (3.35%), Lysinibacillus (2.63%), and Raoultella (34.39%) as principal ureolytic contributors. Soil biocementation trials returned a mean surface strength of 423.3 ± 21.6 psi and a CaCO 3 content of 16.64 ± 1.72%. Heavy metal immobilisation efficiencies reached 99.60% for Cd 2+ , 81.87% for Ni 2+ , 42.47% for Cr 3+ , and 22.47% for Cu 2+ at 10 mg/L. XRD, FTIR, TGA, and DSC collectively confirmed a thermally stable, mineralogically pure biogenic calcite (> 96.7% residue at 894 °C). Collectively, these findings establish RWW-enriched consortia as functionally capable, cost-effective biocatalysts for sustainable MICP, in support of circular economy objectives within tropical urban contexts.

A universal geometric model of egg shape with sine-based deformation - Ching-Wei Cheng; Chia-Chun Lai; Ping-Kun Tsai; Ko-Jung Huang; Cheng-Han Li (Biosystems Engineering, 2026)

Cenozoic plant macrofossils and remains in Taiwan: A review of the literature and fossil record - Yuan-Po Lo; Ching-Yao Li; Jer-Ming Hu (Review of Palaeobotany and Palynology, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Use of AI-mediated image analysis to investigate the influence of environmental factors and recreational scuba diving on fish activity patterns in a marine protected area - Ching-Han Chang; Dong-Lin Li; Li-Shu Chen; Yi-Ta Shao (Regional Studies in Marine Science, 2026)

ICE1 plays a vital role in the development of pollen grains through regulating tapetum degradation and nutrient mobilization in Arabidopsis thaliana - Fa-Li Chang; Jer-Lun Kuo; Meng-Ting Wu; Ching-Hsing Liang; Shiang-Jiuun Chen; Chien-Chih Yang (Plant Molecular Biology, 2026)

Function and transcription of stoS gene of Xanthomonas campestris pathovar campestris - Kai-Xuan Lin; Hsiao-Ching Chang; Chih-En Li; Chao-Tsai Liao; Yi-Min Hsiao (Antonie van Leeuwenhoek, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Phylogeny and Taxonomy of the Coral Reef Maidenhair Fern Adiantum capillus‐veneris subsp. lanyuanum (Pteridaceae) in East Asia - Zhi‐Xiang Chang; Tian‐Chuan Hsu; Xinping Qi; Ching Ming Hsieh; Atsushi Ebihara; Yi‐Han Chang; Yao‐Moan Huang; Li‐Yaung Kuo (New Zealand Journal of Botany, 2026)
Adiantum capillus‐veneris is a species with a worldwide distribution, exhibiting considerable morphological variation, with several infraspecific names applied. Among these infraspecific taxa, A. capillus‐veneris subspecies lanyuanum can be easily distinguished from typical A. capillus‐veneris by its small and 1‐pinnate fronds. This form has been recorded from a few insular populations in Taiwan and Japan, typically inhabiting moist and shaded coral reef cliffs. A chloroplast DNA phylogeny further demonstrates that collections of subsp. lanyuanum across different populations formed a well‐supported clade, and also provides evidence of its genetic distinctiveness and differentiation. Further examination of herbarium specimens and field observations found that, in addition to frond morphology, the rhizome scale differences are also useful for distinguishing the two taxa. As a consequence, A. capillus‐veneris subsp. lanyuanum comb. nov. is proposed as the appropriate taxonomic designation of this taxa and a neotype is designated.

Caffeic acid restores neurogenesis and synaptic integrity under glucolipotoxic stress by suppressing inflammation and pyroptosis - I-Ning Tsai; Xiang-Ning Xie; Ping-En Ko; Yung-Che Tsai; Ching-Chun Chen; Li-Sung Hsu; Chau-Jong Wang (Metabolic Brain Disease, 2026)

Programmable viscoelastic hydrogel enables factor-free adipogenesis of MSCs through mechanotransduction - Tianyue Li; Yanwen Wang; Ziyuan Li; Poh-Ching Tan; Chenghuizi Hu; Jiajun Jin; Shuang-Bai Zhou; Qing-Feng Li; Junji Zhang (Chemical Engineering Journal, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

New features of Peristediidae fishes in the South China Sea - Han Tian; Hsuan‐Ching Ho; Pan Liu; Mingting Li; Wei Xie; Yane Jiang; Xingle Guo; Jiajie Chen; Junpeng Yang; Kedong Yin (Journal of Fish Biology, 2026)
Deep‐diving surveys enable observations of new features of behavioural and functional dimensions of the fish that are typically missing from specimen‐based taxonomy. This study documents three rare armoured searobins (Peristediidae: Scalicus engyceros , Paraheminodus murrayi , Peristedion liorhynchus ) in Xianbei Seamount, Zhongsha Islands and Shenhu Canyon in the South China Sea. Not seen in the dead specimen, the fish in life exhibits bizarre shrimp‐like (in common sense) morphology: the lip barbels formed a laterally rake‐like structure, and the pectoral fins functioned as legs that literally ‘walked’ on the sediment. The fish S. engyceros showed both sideways and backward walking. The paired pectoral fins extrude outwards laterally like flat plates, supporting body balance during walking and swimming. When disturbed, individuals escaped rapidly using both pectoral appendages and tail fins, combining shrimp‐like jerky movements with typical fish swimming. The same species have been reported to occur in both the North and South Pacific oceans, suggesting that their oceanic distribution is by larval dispersal via oceanic currents such as equatorial and Indonesian throughflow currents. The co‐occurrence of three congeners in the same sea may hint local geographic speciation at work after settlement in a seamount habitat.

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Methotrexate-loaded FeAuGd nanoparticles for synergistic magnetic-hyperthermia and chemotherapy - Kayalvizhi Samuvel Muthiah; Lenin Subramanian; Yen-Lin Chen; Udesh Dhawan; Yu-Chien Lin; Ching-Li Tseng; Ren-Jei Chung (Chemical Engineering Journal, 2026)

Cold Atmospheric Plasma as a Non-Thermal and Biocompatible Disinfection Strategy for Ultrasound Transducers - Ching-Yuan Lin; Kuan-Yi Lee; Dong-Jin Li; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Fully coupled conditional simulation of geological and geotechnical variabilities for sparse geotechnical data in three dimensions - Jianye Ching; Hassan Kamyab Farahbakhsh; Jiun-Shiang Wang; Xiang Li; Hui Wang (Engineering Geology, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

Potential role of oocyte-intrinsic fatty acid synthesis in ovarian development of the bigfin reef squid Sepioteuthis lessoniana - Hau-Wen Li; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2026)
In most animals, excess dietary energy is stored as lipids in specialized tissues, such as the liver in vertebrates or the hepatopancreas and fat body in invertebrates, which function as energy reservoirs for reproduction. In cephalopods, however, dietary energy is rapidly mobilized from the digestive gland for growth rather than stored for reproduction. How excess energy is allocated for reproduction activity in cephalopods remains largely unclear. Lipogenesis is initiated by acetyl-CoA carboxylase (ACC), which converts acetyl-CoA derived from dietary carbon sources into malonyl-CoA; subsequent synthesis of saturated fatty acids is catalyzed by fatty acid synthase (FAS). Using the bigfin reef squid as a model, we investigate the role of fas in female development. fas mRNA was highly expressed in ovaries but weak in other tissues, including the lipid-rich digestive gland. fas showed female-biased expression in gonads, with level highest in juvenile ovaries and progressively decreasing to their lowest in mature ovaries. Expression was also high in primary and multiple follicular oocytes but declined in later stages. In situ hybridization and immunohistochemistry confirmed fas mRNA and protein localization in oocytes, particularly in primary and multiple follicular oocytes. In vitro ovarian culture further showed that inhibiting FAS activity enhanced somatic cell proliferation. Together, these findings suggest that squid ovary is a primary site of fatty acid synthesis, supporting early oocyte growth and membrane biogenesis in the absence of dedicated lipid storage tissues. The decline of FAS activity during oogenesis, and the associated reproduction in fatty acid synthesis, may act as a regulatory signal to promote somatic cell proliferation.

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Blood heavy metals content and gut microbiota profile in immature and nesting wild green turtles (Chelonia mydas) - Ming She See; Xin Li Ching; Nurshazwani Razali; Intan Syazwina Asri; Maizah Mohd Abdullah; Joseph Bidai; Mohd Uzair Rusli; Nyuk Ling Ma (Marine Environmental Research, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Unlocking the economic potential of recycling waste fishing nets for textile reproduction - Pei-Chiun Li; Fu-Wei Tsao; Hsiu-Ching Shih; Hwong-wen Ma; Nai-Hua Hou (Ecological Economics, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Photothermal-pancaking synergy in interfacial absorption enables rapid purification of viscous oil-in-water emulsions - Ruoxuan Li; Chaofan Zhu; Ching-Wen Lou; Kaifang Xie; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Chemical Engineering Journal, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Determination of dissolved inorganic carbon export and the controlling factors in small mountainous Rivers, Taiwan - Man-Ching Choi; Pei-Hao Chen; Chi-Wang Tsui; Jr-Chuan Huang; Jun-Yi Lee; Li-Chin Lee (Journal of Hydrology, 2025)

Mechanisms and potential for disinfection byproduct formation from peracetic acid - Jiaqi Li; Ching-Hua Huang (Current Opinion in Environmental Science & Health, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Unleashing instant on-site naked-eye detection by a portable NIR-SPR platform with organic upconversion - Li-Chen Su; Xin-Hui Wang; Chun-Jen Shih; Zhi-Hao Huang; Ying-Feng Chang; Chen-Kai Chang; Chi-Yun Wang; Yu-Ching Huang; Shun-Wei Liu (Chemical Engineering Journal, 2025)

Characteristics of atmospheric CH4, CO2 and CO at a suburban coastal site in Hong Kong - Wai Ming Chan; Dasa Gu; Ka Fung Leung; Yuchen Mai; Sin Ka Mak; Xin Li; Xiangyunong Cao; Zhenxing Liang; Tsz Ching Tse; Zijie Xu; Hao Sun; Heming Bai; et al. (Atmospheric Environment, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Interspecific Competition Reduces Energy Expenditure by Decreasing Intragroup Conflict in a Social Burying Beetle - Bo‐Fei Chen; Yi‐Ching Li; Dustin R. Rubenstein; Angèle Rolland; Syuan‐Jyun Sun; Mark Liu; De‐Pei Chen; Sheng‐Feng Shen (Ecology Letters, 2025)
Assessing the physiological costs of sociality remains challenging due to complex interactions between environmental and social factors. To overcome this challenge, we integrated game theory with empirical research to examine how interspecific competition affects energy expenditure in the cooperatively breeding Asian burying beetle Nicrophorus nepalensis . Our nested tug‐of‐war model made two predictions: beetles facing interspecific competition would experience (1) lower physiological costs due to reduced investment in intragroup conflict, despite increased cooperative effort; and (2) decreasing physiological cost differences between dominance ranks. Using thermal imaging, we analysed body temperature as a proximal indicator of thermogenic effort during carcass work. Results supported our model's two key predictions: beetles competing with blowflies exhibited lower body temperatures, with less pronounced temperature differences between social ranks. Thus, reduced social conflict outweighs the energetic costs of increased cooperation in the face of external threats, providing insights into how environmental conditions shape energy allocation in social species.

Cover Image, Volume 28, Issue 12 - Bo‐Fei Chen; Yi‐Ching Li; Dustin R. Rubenstein; Angèle Rolland; Syuan‐Jyun Sun; Mark Liu; De‐Pei Chen; Sheng‐Feng Shen (Ecology Letters, 2025)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Unraveling urban plant diversity: The independent effects of plant species richness and greenness on health - Chia-Ching Wu; Chun-Yen Chang; Brian Deal; Dongying Li; William C. Sullivan (Urban Forestry & Urban Greening, 2025)

Removal of oil/grease and anionic surfactants in carwash wastewater using an electrocoagulation-flotation (ECF) process: a pilot-scale study - Jung-Ming Wu; Wen-Hui Kuan; Li-Wei Ke; Ching-Yao Hu (Journal of Water Process Engineering, 2025)

Plasma-guided green synthesis of crystalline graphene quantum dots for broad-spectrum antiviral applications - Ren-Jie Weng; Li-Syuan Wu; Darwin Kurniawan; Ching-Tzu Chang; Ming-Han Tsai; Wei-Hung Chiang (Chemical Engineering Journal, 2025)

Natural lignan justicidin A-induced mitophagy as a targetable niche in bladder cancer - Kai-Hsun Chang; Hsin-Chih Chen; Ching-Ying Chen; Shu-Ping Tsai; Man-Yuan Hsu; Pao-Yuan Wang; Shan-Ying Wu; Chun-Li Su (Chemico-Biological Interactions, 2025)

Metabolic Plasticity and Cancer Stem Cell Metabolism: Exploring the Glycolysis-OXPHOS Switch as a Mechanism for Resistance and Tumorigenesis - Li Qing Keoh; Ching-Feng Chiu; Thamil Selvee Ramasamy (Stem Cell Reviews and Reports, 2025)

Immune signaling and drought tolerance mediated by NDR1-AHA5 regulation of H⁺–ATPase, guard cells, and homeostasis - Yi-Ju Lu; Huan Chen; Alex Corrion; Pai Li; Saroopa Samaradivakara; Ching Man Wai; Hikaru Sakamoto; Patrícia Santos; Robert VanBuren; Yongsig Kim; Brad Day; Ilker Buyuk (Plant Cell Reports, 2025)

Skin penetration enhancers: Mechanistic understanding and their selection for formulation and design - Yee Shan Sim; Li Ching Wong; Soo Chin Yeoh; Abdulsalam Almashhadani; Bilal Harieth Alrimawi; Choon Fu Goh (Drug Delivery and Translational Research, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Upcycling waste PET into benzoxazines with simultaneously low curing temperatures and high thermal stability - Dula Daksa Ejeta; Meng-Xuan Li; Yu-Kuan Hsu; Muhammad Javed Iqbal; Ching-Hsuan Lin (Chemical Engineering Journal, 2025)

Effects of Cyclic Stretch on Chondrogenic Differentiation of Rat Adipose-Derived Stem Cells Cultured on Type-I Collagen Coated PDMS Membrane - Hung-Maan Lee; Hui-Ying Li; Yi-Ho Hsieh; Lassina Barro; Ching-Yi Cheng; Ming-Fa Hsieh (Journal of Medical and Biological Engineering, 2025)

A Review of Atmospheric Micro/Nanoplastics: Insights into Source and Fate for Modelling Studies - Fei Jiang; Chengze Gao; Arthur W. H. Chan; David O. Topping; Hongliang Zhang; Weijun Li; Hugh Coe; Xiaohong Liu; Joseph Ching; Zhonghua Zheng (Current Pollution Reports, 2025)
Purpose of Review Micro/nanoplastics (MNPs), as emerging pollutants, have attracted increasing attention due to their potential adverse effects on human health, ecosystems, and climate. The rapid, turbulent, and large-scale nature of atmospheric transport facilitates both horizontal and vertical movement of MNPs over long distances within a short time, largely independent of topographical constraints, thereby accelerating their global cycle and exacerbating their impacts. Despite growing interest, our understanding of the atmospheric lifecycle of MNPs remains limited. This review aims to synthesise recent advances in understanding the atmospheric lifecycle of MNPs, including their emission sources, long-range transport characteristics, and driving mechanisms. It also evaluates the key sources of uncertainty—particularly those related to emission flux estimates—and provides corresponding recommendations for future research. Recent Findings Current research on the atmospheric processes of MNPs primarily relies on a combination of observational data and numerical modelling. Two major uncertainties in atmospheric micro/nanoplastic (AMNP) emissions persist: the wide variability in marine emission estimates, which span four orders of magnitude, and the unresolved question of whether terrestrial or marine sources are the dominant contributors to AMNP emissions. Furthermore, this review highlights critical factors driving these uncertainties, including limited data availability, inconsistencies in observational methodologies, oversimplified simulations, and gaps in understanding atmospheric cycling mechanisms. Additionally, variations in the particle size ranges targeted by different observational and modelling studies hinder cross-comparisons and model evaluations, representing another important source of uncertainty. Summary AMNP research is constrained by multiple uncertainties that hinder a comprehensive understanding of their emissions, transport, and fate. To address these issues, we call for establishing a global network of standardised observations, improving sampling and simulation practices, and incorporating artificial intelligence. These strategies will enhance our understanding of the complete atmospheric cycle of MNPs, paving the way for more effective environmental management and better-informed policy decisions.

Non–Hermitian entanglement dip from scaling-induced exceptional criticality - Sirui Liu; Hui Jiang; Wen-Tan Xue; Qingya Li; Jiangbin Gong; Xiaogang Liu; Ching Hua Lee (Science Bulletin, 2025)

Community shift of aquatic insects following waste-water treatment implementation at Dongda Creek, Taichung City, Taiwan - Lilibeth A. Bucol; Ching-Chen Lee; Lan-Wai Yeh; Li-Wei Wu; Jyh-Min Chiang (Journal of Asia-Pacific Entomology, 2025)

Electron transfer centers facilitate the degradation of antibiotics with an O-doped walnut shell biochar/periodate system - Xi Zhang; Alina Liyakat; Mohammadreza Kamali; Junwei Li; Bart Van der Bruggen; Ching-Hua Huang; Deirdre Cabooter; Raf Dewil (Chemical Engineering Journal, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

Highly hydrovoltaic fabrics based on water evaporation drive for self-powered wearable - Xiaoyang Zhang; Xuefei Zhang; Hai-Tao Ren; Ting-Ting Li; Ching-Wen Lou (Chemical Engineering Journal, 2025)

Causes, emission characteristics, and health risks of persistent free radicals and reactive oxygen species in PM2.5 produced by smoldering incense - Yu-Chieh Wang; Bo-Yu Chen; Yen-Hsien Li; Tzu-Hsien Tseng; Chon-Lin Lee; Wei-Min Ching (Atmospheric Pollution Research, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunology, 142: 109,134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa by product as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunol. (2023) 142 109134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Adult head circumference and the risk of cancer: a retrospective cohort study - Suhas Krishnamoorthy; Jonathan K. L. Mak; Kathryn C. B. Tan; Gloria H. Y. Li; Ching-Lung Cheung (Cancer Causes & Control, 2025)
Purpose Cancer-related genes and pathways have recently been implicated in a genome-wide meta-analysis of head size. In the current study, we aimed to evaluate the association between adult head circumference and the risk of cancer. Methods This is a cohort study using data from the Hong Kong Osteoporosis Study, where 1,301 participants aged 27–96 years with head circumference measured between 2015 and 2019, and without a history of cancer, were followed up to 15 January 2024. Incident cancers were identified using electronic medical records from a territory-wide database. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using Cox proportional hazards regression, adjusting for age, sex, height, weight, education, smoking, alcohol drinking, physical activity, and family history of cancer, as well as accounting for familial clustering. Results The median head circumference was 53 cm (interquartile range [IQR]: 51–54) and 54 cm (IQR: 53–55) for women and men, respectively. During a median follow-up of 6.9 years, 66 individuals were diagnosed with cancer. In the adjusted model, a larger head circumference was associated with an increased risk of any cancer (HR per cm increase: 1.17; 95% CI 1.00–1.36). Results remained similar when adjusting for waist-to-hip ratio instead of weight or when additionally adjusting for serum calcium and phosphorus levels. When stratified by cancer sites, head circumference was most strongly associated with colorectal cancer (HR per cm increase: 1.81; 95% CI 1.14–2.90) and prostate cancer (HR per cm increase: 1.58; 95% CI 1.16–2.16). Conclusion Head circumference is positively associated with the risk of cancer independently of height, weight, and other cancer risk factors.

A potential closed-loop reutilization of iron sludge for wastewater treatment through the solid state reaction with spent coffee grounds - Kun Qin; TsingHai Wang; Wei-Tong Li; Zi-Ying Lu; Cheng-Yu Li; Wei-Fan Kuan; Jenn-Fang Su; Ching-Lung Chen (Process Safety and Environmental Protection, 2025)

Analyzing the effects of data splitting and covariate shift on machine learning based streamflow prediction in ungauged basins - Pin-Ching Li; Sayan Dey; Venkatesh Merwade (Journal of Hydrology, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Bio-active metabolites from Chinese Medicinal Herbs for treatment of skin diseases - Xiao Xiao Wu; Siu Kan Law; Hui Ma; Zhou Jiang; Yi Fan Li; Dawn Ching Tung Au; Chun Kwok Wong; Di Xian Luo (Natural Product Research, 2025)

Occurrence & characterization of Staphylococcus aureus from ready-to-eat (RTE), and cooked food in Singapore: A retrospective analysis - Ye Htut Zwe; Roshini Devi Mohan; Si Jia Lim; Wai Ching Lai; Kae Hwan Sim; Yu Lee Leyau; Ker Lew; Joachim Mun Choy Chua; Kyaw Thu Aung; Kern Rei Chng; Yuan Sheng Wu; Joanne Sheot Harn Chan; et al. (International Journal of Food Microbiology, 2025)

Singular value decomposition of near-field electromagnetic data for compressing and accelerating deep neural networks in the prediction of geometric parameters for through silicon via array - Song-En Chen; Eugene Su; Chih-Chung Wang; Jia-Han Li; Chao-Ching Ho (Computer Physics Communications, 2025)

Preliminary analysis of landslides induced by the 3 April 2024 Mw 7.4 Hualien, Taiwan earthquake - Yi Chen; Chuang Song; Zhenhong Li; Bo Chen; Chen Yu; Jyr-Ching Hu; Xingmin Cai; Shuang Zhu; Qianwen Wang; Yixin Ma; Changjun Gu; Suju Li; et al. (Landslides, 2025)

Blood and cloacal microbiome profile of captive green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata): Water quality and conservation implications - Xin Li Ching; Syamsyahidah Samsol; Mohd Uzair Rusli; Mohamad Aqmal-Naser; Joseph Anak Bidai; Christian Sonne; Xin Wu; Nyuk Ling Ma (Chemosphere, 2025)

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Essential amino acids and branched-chain amino acids are associated with skeletal muscle and inflammatory parameters in older age - Ching Wah Donna Li; Catrin Herpich; Ulrike Haß; Bastian Kochlik; Daniela Weber; Tilman Grune; Kristina Norman (Biogerontology, 2025)
Aging is associated with a decline in muscle mass and function, increasing the risk of adverse health outcomes. Amino acid profiling has emerged as a potential tool for assessing skeletal muscle health. This study examines the associations between fasting plasma amino acids, muscle function, and inflammation in healthy older and young adults. Data from 131 participants (101 older adults, 71.5±4.9 years; 30 young adults, 25.5±3.9 years) were analyzed. Skeletal muscle mass was assessed using bioimpedance analysis, and hand grip strength was measured with a dynamometer. Plasma amino acids, kynurenine, and inflammatory markers (CRP, IL-6) were quantified using ultraperformance liquid chromatography with tandem mass spectrometry and commercial immunosorbent assays, respectively. Older adults exhibited lower levels of glutamic acid, isoleucine, leucine, phenylalanine, kynurenine, and kynurenine-to-tryptophan (KYN:TRP) ratio compared to younger individuals (all p

Akkermansia muciniphila: promises and pitfallsfor next-generation beneficial microorganisms - Yantong Liu; Zonglun Li; Sze Ching Lee; Shurui Chen; Feifei Li (Archives of Microbiology, 2025)

Pathological and biochemical effects of polyethylene microplastic exposure in hydrothermal vent crab, Xenograpsus testudinatus - Mark June S. Consigna; Li-Chun Tseng; Chi Chou; Ching-Wen Huang; Yi-Ta Shao; Jiang-Shiou Hwang (Marine Pollution Bulletin, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Triboelectric Nanogenerator based on superstructure MoS2 for energy harvesting and human sensing - Hao Zhao; Jia-Horng Lin; Hai-Tao Ren; Hao-kai Peng; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

A comprehensive optimization of highly efficient MA-Free wide-bandgap perovskites for 4-T Perovskite/Silicon tandem solar cells - Yu-Ching Huang; Sheng-Wen Huang; Chia-Feng Li; Shih-Han Huang; Feng-Yu Tsai; Wei-Fang Su (Chemical Engineering Journal, 2025)

Regional sea level budget around Taiwan and Philippines over 2002‒2021 inferred from GRACE, altimetry, and in-situ hydrographic data - Wen-Hau Lan; Chi-Ming Lee; Chung-Yen Kuo; Li-Ching Lin; Eko Yuli Handoko (Journal of Geodesy, 2025)
The regional sea level budget and interannual sea level changes around Taiwan and Philippines are studied using altimetry, GRACE, and in-situ hydrographic data during 1993‒2021. Results show that the average sea level trend around Taiwan and Philippines during 1993–2021 derived from the altimetric data is 3.6 ± 0.2 mm/yr. Over 2002–2021, the study shows closure of sea level budget in the eastern ocean of Taiwan and Philippines within the observed data uncertainties, and the ocean mass accounts for 88%–100% of the observed sea level rise. In contrast, the sea level budget is not closed in the western ocean of Taiwan and Philippines, probably due to the lack of complete coverage by in-situ ocean observing systems. In addition, both regional sea level anomalies and their steric component around Taiwan and Philippines exhibit pronounced interannual and decadal variabilities. The trade wind stress associated with El Niño–Southern Oscillation and Pacific Decadal Oscillation offers a compelling explanation for the interannual and decadal signals of sea level anomalies in the southern ocean of Taiwan, with negative correlations of − 0.78 to − 0.64, indicating that trade wind stress makes a negative contribution to interannual-to-decadal sea level variability. In the northwestern ocean of Taiwan, the sea level variation is strongly influenced by the local monsoon system and shallow bathymetry with an annual amplitude of 90.3 ± 2.9 mm, larger than those in other regions around Taiwan and Philippines, where ocean mass is dominant with a high correlation with the sea level (+ 0.75 to + 0.78).

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Silicon quantum dot-enhanced thin-film nanocomposite membranes for efficient alcohol dehydration via pervaporation: A sustainable approach - Chih-Ching Huang; Marwin R. Gallardo; Chi-Lan Li; Shu-Hsien Huang; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2024)

Effects of silane hydrolysis time on the physicochemical properties of bioplastics based on starch and epoxidized soybean oil - Jianlei Yang; Shicai Xu; Yern Chee Ching; Cheng Hock Chuah; Rui Wang; Chunhui Li; Yunwei Wei; Guoying Liang (Food Chemistry, 2024)

Seasonal variation and origins of C1–C5 alkyl nitrates: A year-long study at a Hong Kong coastal site - Hao Sun; Dasa Gu; Zijie Xu; Xin Feng; Xiangyunong Cao; Yuchen Mai; Xin Li; Ho Wun Lee; Ka Fung Leung; Tsz Ching Tse; Wai Ming Chan; Sin Ka Mak (Atmospheric Environment, 2024)

Nitrogen source and availability regulate plastic population dynamics in the marine diatom Thalassiosira weissflogii - Zhenzhen Li; Hau Ching Luk; Bovern Suchart Arromrak; Juan Diego Gaitan-Espitia (Marine Environmental Research, 2024)

Maintaining KEAP1 levels in retinal pigment epithelial cells preserves their viability during prolonged exposure to artificial blue light - Ching-Hao Li; Tsung-Min Yang; Ida Fitriana; Te-Chao Fang; Liang-Huan Wu; George Hsiao; Yu-Wen Cheng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Self-regenerative Ni/SiO2 for dry reforming of methane (DRM): 1000 h-longevity assessment and operando insights to coke removal under N2 atmosphere - Li-Wei Chen; Kim Hoong Ng; Liang-Ching Hsu (Chemical Engineering Journal, 2024)

Novel personal cooling textiles revolutionizing human thermal management: principles, designs and applications - Xianjin Hu; Ting-Ting Li; Bingbing Shou; Letian Li; Hai-Tao Ren; Ching-Wen Lou (Chemical Engineering Journal, 2024)

A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

Investigation of verapamil-induced cardiorenal dysfunction and compensatory ion regulation in zebrafish embryos - Jiun-Lin Horng; Bu-Yuan Hsiao; Wen-Ting Lin; Tzu-Ting Lin; Ching-Yen Chang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

A case-control study of behavioural and built environment determinants of COVID-19 transmission in sheltered markets - Jiayu Li; Junjing Yang; Bindhu Unni; Rowena Yap; Jue Tao Lim; Mohammad Nazeem; Joanna Shen; Yee Leong Teoh; Lee Ching Ng; Shuzhen Sim (Building and Environment, 2024)

Longitudinal Morphometric Changes in the Corticospinal Tract Shape After Hemorrhagic Stroke - Seth B. Boren; Sean I. Savitz; Nicole Gonzales; Khader Hasan; Andrea Becerril-Gaitan; Vahed Maroufy; Yuan Li; James Grotta; Emily A Steven; Ching-Jen Chen; Clark W. Sitton; Jaroslaw Aronowski; et al. (Translational Stroke Research, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Revisiting the synergistic oxidation of peracetic acid and permanganate(Ⅶ) towards micropollutants: The enhanced electron transfer mechanism of reactive manganese species - Yufei Shi; Shaoze Xiao; Yajie Qian; Ching-Hua Huang; Jiabin Chen; Nan Li; Tongcai Liu; Yalei Zhang; Xuefei Zhou (Water Research, 2024)

Bioinspired multiscale hierarchical structure enables solar-thermal conversion for low-temperature aqueous electrochromic device - Qi Zhao; Xue Chen; Qiming Zhu; Chin Ho Kirk; Jianguo Sun; Li Wang; Shuai Guo; Swee Ching Tan; Yanfeng Gao; John Wang (Chemical Engineering Journal, 2024)

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Winter harvesting reduces methane emissions and enhances blue carbon potential in coastal phragmites wetlands - Ying Huang; Qingyu Jia; Jiangtao Wang; Sung-Ching Lee; Xianglan Li; Xiuzhen Li; Jianwu Tang (Science of The Total Environment, 2024)

Energy transition: Cap-and-trade and carbon capture and storage for achieving net-zero emissions with sustainable insurance - Shi Chen; Yuqi Li; Jyh-Horng Lin; Ching-Hui Chang (Journal of Environmental Management, 2024)

Retraction Note: Assessing the impact of green fiscal policies and energy poverty on energy efficiency - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Tai Duc Tran; Li Li (Environmental Science and Pollution Research, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Testing the moderated mediation effect of recreation safety climate on the interrelationship of serious leisure, recreation involvement, and flow experience - Tien-Ming Cheng; Ching-Yi Hsu; Shan-Ni Li (Journal of Outdoor Recreation and Tourism, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Physicochemical and release properties of anthocyanin gastric floating tablets colloidized with κ-carrageenan/metal ions - Kai-Ching Yuan; Yi-Chan Chiang; Po-Hsien Li; Po-Yuan Chiang (Food Hydrocolloids, 2024)

Meteotsunamis in the Tamsui River estuary, Taiwan - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Estuarine, Coastal and Shelf Science, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Determination of the Elemental Iodine in Human Breast Milk by Inductively Coupled Plasma mass Spectrometry - Chun-Jui Huang; Jia-Zhen Li; Chii-Min Hwu; Harn-Shen Chen; Chang-Ching Yeh; Fan-Fen Wang; Chen-Chang Yang (Biological Trace Element Research, 2024)

Treating boron-containing wastewater by electrocoagulation-flotation (ECF) process with the stepwise addition of anionic surfactants - Yu-Jung Liu; Chia-Hui Yen; Yueh-Feng Li; Ching-Yao Hu (Journal of Water Process Engineering, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Rosette-like (Ni,Co)Se2@Nb2CTx MXene heterostructure with abundant Se vacancies for high-performance flexible supercapacitor electrodes - Baolei Shen; Xianjin Hu; Hai-Tao Ren; Hao-Kai Peng; Bing-Chiuan Shiu; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2024)

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Separation and enrichment of tricolor phosphors in waste phosphors through liquid–liquid–powder extraction method and its benefit evaluation for recovery - Li Pang Wang; Jun Ming Hou; Yan Jhang Chen; Bu Ching Tseng; Sandhya Babel (Minerals Engineering, 2024)

Enhance electrocoagulation-flotation (ECF) removal efficiency perfluorohexanoic acid (PFHxA) by adding surfactants - Yueh-Feng Li; Chung-Yu Ho; Yu-Jung Liu; Yu-Chi Lee; Ching-Yao Hu; Shang-Lien Lo (Journal of Environmental Chemical Engineering, 2024)

Photothermal-driven pH-responsive fiber composite membrane for oil-wastewater purification - Shuxia Li; Jia-Horng Lin; Hai-Tao Ren; Bing-Chiuan Shiu; Fei Sun; Ching-Wen Lou; Ting-Ting Li (Journal of Environmental Chemical Engineering, 2024)

Medulla Tetrapanacis water extract alleviates inflammation and infection by regulating macrophage polarization through MAPK signaling pathway - Carsten Tsun-Ka Kwok; Franklin Wang-Ngai Chow; Karry Yuen-Ching Cheung; Xiao-Yi Zhang; Daniel Kam-Wah Mok; Yiu-Wa Kwan; Gabriel Hoi-Huen Chan; George Pak-Heng Leung; Ka-Wang Cheung; Simon Ming-Yuen Lee; Ning Wang; Jing-Jing Li; et al. (Inflammopharmacology, 2024)

A 16-year meteotsunami climatology in the coastal areas of southern Asia-Pacific Ocean - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Frontiers in Marine Science, 2024)
This study presents the meteotsunami behavior in response to different storm types in the coasts of southern Asia-Pacific Ocean from 16 years water level records. Through the size- frequency analysis, the dangerous meteotsunami, wave height exceeding 0.3 m, can occur up to 44 events per year. Notably, during the extreme waves of the 2007 event, wave heights reached approximately 0.9-1.5 m in the Taiwan Strait and the western coastal areas of Taiwan. We have classified storms into six types by radar reflectivity images and satellite-derived precipitation. Findings indicate that predicted wave heights caused by bows and typhoons could reach hazardous magnitude of exceeding 2 m in a 100-yr interval. Spatial and temporal analysis reveals that meteotsunami occurrences are most frequent in the western regions during the winter to early spring months (December to April). Of all meteotsunami occurrences, cluster storms are identified as the most prevalent atmospheric forcing, accounting for 60% of meteostunamis. Typhoons have a 20% association with meteotsunamis along the east coasts of Taiwan during late summer to autumn. On the east coasts, typhoon type-induced events may be attributed to the combination effect of meteotsunamis and infra-gravity waves. Overall, this study provides the first comprehensive examination of meteotsunami-storm characteristics and their associated hazard risks in the coastal areas of the southern Asia-Pacific Ocean.

A Bispecific Modeling Framework Enables the Prediction of Efficacy, Toxicity, and Optimal Molecular Design of Bispecific Antibodies Targeting MerTK - Ran Li; Edward Dere; Mandy Kwong; Mingjian Fei; Rutwij Dave; Shabkhaiz Masih; Joy Wang; Erin McNamara; Haochu Huang; Wei-Ching Liang; Leah Schutt; Amrita V. Kamath; et al. (The AAPS Journal, 2024)
Inhibiting MerTK on macrophages is a promising therapeutic strategy for augmenting anti-tumor immunity. However, blocking MerTK on retinal pigment epithelial cells (RPEs) results in retinal toxicity. Bispecific antibodies (bsAbs) containing an anti-MerTK therapeutic and anti-PD-L1 targeting arm were developed to reduce drug binding to MerTK on RPEs, since PD-L1 is overexpressed on macrophages but not RPEs. In this study, we present a modeling framework using in vitro receptor occupancy ( RO ) and pharmacokinetics (PK) data to predict efficacy, toxicity, and therapeutic index ( TI ) of anti-MerTK bsAbs. We first used simulations and in vitro RO data of anti-MerTK monospecific antibody (msAb) to estimate the required MerTK RO for in vivo efficacy and toxicity. Using these estimated RO thresholds, we employed our model to predict the efficacious and toxic doses for anti-MerTK bsAbs with varying affinities for MerTK. Our model predicted the highest TI for the anti-MerTK/PD-L1 bsAb with an attenuated MerTK binding arm, which was consistent with in vivo efficacy and toxicity observations. Subsequently, we used the model, in combination with sensitivity analysis and parameter scans, to suggest an optimal molecular design of anti-MerTK bsAb with the highest predicted TI in humans. Our prediction revealed that this optimized anti-MerTK bsAb should contain a MerTK therapeutic arm with relatively low affinity, along with a high affinity targeting arm that can bind to a low abundance target with slow turnover rate. Overall, these results demonstrated that our modeling framework can guide the rational design of bsAbs. Graphical Abstract

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Antimicrobial photodynamic therapy encapsulation technology: Frontier exploration and application prospects of novel antimicrobial technology - Xianjin Hu; Bingbing Shou; Lu Yang; Letian Li; Hai-Tao Ren; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2023)

Machine learning-based monosaccharide profiling for tissue-specific classification of Wolfiporia extensa samples - Shih-Yi Hsiung; Shun-Xin Deng; Jing Li; Sheng-Yao Huang; Chen-Kun Liaw; Su-Yun Huang; Ching-Chiung Wang; Yves S.Y. Hsieh (Carbohydrate Polymers, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei) - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models - Ka Ka Ting; Paul Coleman; Hani Jieun Kim; Yang Zhao; Jocelyne Mulangala; Ngan Ching Cheng; Wan Li; Dilini Gunatilake; Daniel M. Johnstone; Lipin Loo; G. Gregory Neely; Pengyi Yang; et al. (GeroScience, 2023)
Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells display altered VE-cadherin expression and loss of cell junction formation and increased permeability. Consistent with this, senescent endothelial cells in APP/PS1 mice are present at areas of vascular leak that have decreased claudin-5 and VE-cadherin expression confirming BBB breakdown. Furthermore, single cell sequencing of endothelial cells from APP/PS1 transgenic mice confirms that adhesion molecule pathways are among the most highly altered pathways in these cells. At the pre-plaque stage, the vasculature shows significant signs of breakdown, with a general loss of VE-cadherin, leakage within the microcirculation, and obvious pericyte perturbation. Although senescent vascular cells were not directly observed at sites of vascular leak, senescent cells were close to the leak area. Thus, we would suggest in AD that there is a progressive induction of senescence in constituents of the neurovascular unit contributing to an increasing loss of vascular integrity. Targeting the vasculature early in AD, either with senolytics or with drugs that improve the integrity of the BBB may be valid therapeutic strategies.

First principal observation documenting the three-dimensional uptake of cadmium and spatial distribution of cadmium hydroxyapatite mineral in bone char - Partha Pratim Biswas; Jagat Rathod; Ching-Yu Chiang; Biqing Liang; Chun-Chieh Wang; Yao-Chang Lee; Yu-Chun Chuang; Prakash C. Loni; Wei-Hsin Chen; Shan-Li Wang (Chemosphere, 2023)

Boron removal from high sulfate-containing coal-fired power plant wastewater by an ultrasound/bipolar electrocoagulation process with aluminum electrodes - Yueh-Feng Li; Yu-Jung Liu; Chia-Hui Yen; Ching-Yao Hu (Journal of Environmental Chemical Engineering, 2023)

Hybridize magnesium-iron layered double hydroxide with biopolymers to develop multiple pathways for phosphate sorption and release: A potential slow release phosphorus fertilizer - Wen-Hui Li; Liang-Ching Hsu; Yu-Min Tzou; Yi-Chun Chen; Heng Yi Teah; Yu-Yu Kung; Han-Yu Chen; Yu-Ting Liu (Chemical Engineering Journal, 2023)

Capture of colloidal fine suspended particle by aquatic vegetation under rainfall - Congrong Yu; Xiuhui Ye; Ying Li; Ching-Sheng Huang; Zhongbo Yu; Gang Chen; Xiaoxiao Hao (Science of The Total Environment, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

Chitosan-based antibacterial microspheres loaded multifunctional Janus composite membranes with unidirectional biofluid transport, antioxidant and pH-responsive monitoring - Ting-Ting Li; Li Sun; Ying Zhang; Bing-Chiuan Shiu; Hai-Tao Ren; Hao-Kai Peng; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Rat Hair Metabolomics Analysis Reveals Perturbations of Unsaturated Fatty Acid Biosynthesis, Phenylalanine, and Arachidonic Acid Metabolism Pathways Are Associated with Amyloid-β-Induced Cognitive Deficits - Tian-Hoe Tan; Shih-Wen Li; Chih-Wei Chang; Yuan-Chih Chen; Yu-Hsuan Liu; Jui-Ti Ma; Ching-Ping Chang; Pao-Chi Liao (Molecular Neurobiology, 2023)
Hair is a noninvasive valuable biospecimen for the long-term assessment of endogenous metabolic disturbance. Whether the hair is suitable for identifying biomarkers of the Alzheimer’s disease (AD) process remains unknown. We aim to investigate the metabolism changes in hair after β-amyloid (Aβ 1-42 ) exposure in rats using ultra-high-performance liquid chromatography-high-resolution mass spectrometry–based untargeted and targeted methods. Thirty-five days after Aβ 1-42 induction, rats displayed significant cognitive deficits, and forty metabolites were changed, of which twenty belonged to three perturbed pathways: (1) phenylalanine metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis— l -phenylalanine, phenylpyruvate, ortho-hydroxyphenylacetic acid, and phenyllactic acid are up-regulated; (2) arachidonic acid (ARA) metabolism—leukotriene B4 (LTB4), arachidonyl carnitine, and 5(S)-HPETE are upregulation, but ARA, 14,15-DiHETrE, 5(S)-HETE, and PGB2 are opposite; and (3) unsaturated fatty acid biosynthesis— eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), FA 18:3 + 1O, and FA 18:3 + 2O are downregulated. Linoleic acid metabolism belonging to the biosynthesis of unsaturated fatty acid includes the upregulation of 8-hydroxy-9,10-epoxystearic acid, 13-oxoODE, and FA 18:2 + 4O, and downregulation of 9(S)-HPODE and dihomo-γ-linolenic acid. In addition, cortisone and dehydroepiandrosterone belonging to steroid hormone biosynthesis are upregulated. These three perturbed metabolic pathways also correlate with cognitive impairment after Aβ 1-42 stimulation. Furthermore, ARA, DHA, EPA, l -phenylalanine, and cortisone have been previously implicated in the cerebrospinal fluid of AD patients and show a similar changing trend in Aβ 1-42 rats’ hair. These data suggest hair can be a useful biospecimen that well reflects the expression of non-polar molecules under Aβ 1-42 stimulation, and the five metabolites have the potential to serve as novel AD biomarkers.

On constructing limits-of-acceptability in watershed hydrology using decision trees - Abhinav Gupta; Rao S. Govindaraju; Pin-Ching Li; Venkatesh Merwade (Advances in Water Resources, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Inferring faulting model using InSAR deformation differencing vector: application to the 2014 Napa earthquake - Ying-Hui Yang; Hao-Liang Li; Qiang Chen; Jing Chen; Jyr-Ching Hu; Xiao-Yun Li; Qiang Xu (Journal of Geodesy, 2023)

Long‐term variability in the fish assemblage around Japan over the last century and early warning signals of regime shifts - Yongjun Tian; Caihong Fu; Akihiko Yatsu; Yoshiro Watanabe; Yang Liu; Jianchao Li; Dan Liu; Yumeng Pang; Jiahua Cheng; Ching‐Hsein Ho; Shuyang Ma (Fish and Fisheries, 2023)
The marine ecosystems around Japan are very productive and have typical wasp‐waist structure dominated by small pelagic fishes such as sardine, exhibiting large low‐frequency fluctuations in biomass. Whereas studies on the variability in abundance of individual species such as sardine and anchovy are popular, only a few studies focused on the long‐term variability of fish assemblage around Japan. In this study, 13 species/taxa ranging from small forage to large predatory species and from warm‐ to cold‐water species were selected to indicate essential characteristics of the fish assemblage and their drivers were analysed based on fishery, oceanographic and climatic data sets from 1901 to 2018. Results show that two outstanding peaks during the 1930s and 1980s were characterized by abundant sardine. Additionally, species composition showed high similarities during similar temperature regimes while exhibiting contrasts during different temperature regimes. Variations and regime shifts in dominant patterns and fish community indices coincided well with the Atlantic Multidecadal Oscillation (AMO) and regional sea surface temperature (SST). Furthermore, gradient forest analysis identified AMO and regional SSTs as most important predictors of dominant patterns and fish community indices, suggesting that the decadal and multidecadal variability in the fish assemblage around Japan was forced by basin‐scale climate variability as inherent in the AMO through its connections with regional SSTs. Autocorrelation coefficient demonstrated that the ecological indicators have the potential to be early warning signals of regime shifts, which suggests the possibility of coming cold regime since around 2015 and has important implications for fisheries management.

Field trial assessing the antimicrobial decontamination efficacy of gaseous ozone in a public bus setting - Erica Sena Neves; Cheng Teng Ng; Han Bin Pek; Vanessa Shi Li Goh; Roslinda Mohamed; Sheereen Osman; Yi Kai Ng; Sharain Abdul Kadir; Mohammad Nazeem; Alan She; Glenndle Sim; Joel Aik; et al. (Science of The Total Environment, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Preparation and study of bark-like MXene based high output power hydroelectric generator - Xiaoyang Zhang; Yanting Wang; Xuefei Zhang; Ching-Wen Lou; Jia-Horng Lin; Ting-Ting Li (Chemical Engineering Journal, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Free-standing [0 0 1]-oriented one-dimensional crystal-structured antimony selenide films for self-powered flexible near-infrared photodetectors - Xixing Wen; Zonghuan Lu; Bingxiang Li; Gwo-Ching Wang; Morris A. Washington; Qiang Zhao; Toh-Ming Lu (Chemical Engineering Journal, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Cationic surfactants influencing the enhancement of energy efficiency for perfluorooctanoic acid (PFOA) removal in the electrocoagulation-flotation (ECF) system - Yueh-Feng Li; Ting Fang; Yu-Chi Lee; Yu-Jung Liu; Ching-Yao Hu; Shang-Lien Lo (Chemosphere, 2023)

Metabolic fate of black raspberry polyphenols in association with gut microbiota of different origins in vitro - Yat-Tin Chan; Jiating Huang; Ho-Ching Wong; Jun Li; Danyue Zhao (Food Chemistry, 2023)

Health Risk of Infants Exposed to Lead and Mercury Through Breastfeeding - Yung-Chieh Lin; Wei-Hsiang Chang; Tsun-Ching Li; Osuke Iwata; Hsiu-Ling Chen (Exposure and Health, 2023)
Donor milk from the human milk bank is important for vulnerable infants without their mothers’ own milk. Longitudinal changes in toxic metals in donor milk has not been reported. This study aimed to assess the effect of donors’ demographic characteristics, life habits and dietary habits on the concentration of metals in breastmilk donated to a human milk bank and to assess the health risk of lead (Pb) and mercury (Hg) exposure of donor mothers’ offspring through breastfeeding and the vulnerable recipients. A total of 228 samples, which were longitudinally donated to the human milk bank by 39 donors, were selected specifically to assess the levels of Pb, Hg, and MeHg. Donors’ offspring were also enrolled as mother-infant-dyads to monthly obtain the milk consumption and body weight. The results showed significant differences in the infant risk in exclusive breastfeeding months. The average Pb level of breast milk was 6.49 ± 5.23 µg/L (mean ± standard deviation), and the Hg level was 0.76 ± 0.98 µg/L. The sources of these toxins—residential districts, cleaning products, cosmetics, drinking water, viscera, eggs, seafood, and canned food—have a significant influence on the concentration of toxic metals in human milk. This study showed an unacceptable non-cancerous health risk (95th percentile hazard index, HI = 1.37 > 1) for Pb and Hg. In the future, the breast milk offered by the bank should be strictly monitored, especial for Pb, to ensure high-quality donor milk for vulnerable recipients but also donor mothers’ offspring who depend on it. Graphical Abstract

Enhancing mechanical and photocatalytic properties by surface microstructure regulation of TiO2 nanofiber membranes - Xilin Liao; Hai-Tao Ren; Baolei Shen; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemosphere, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Association between cold weather, influenza infection, and asthma exacerbation in adults in Hong Kong - Xi Xiong; Yuchen Wei; Holly Ching Yu Lam; Carlos King Ho Wong; Steven Yuk Fai Lau; Shi Zhao; Jinjun Ran; Conglu Li; Xiaoting Jiang; Qianying Yue; Wei Cheng; Huwen Wang; et al. (Science of The Total Environment, 2023)

Sputter-deposited nickel nanoparticles on Kevlar fabrics with laser-induced graphene for efficient solar evaporation - Shuaihang Zhu; Zhiwei Lei; Yuejie Dou; Ching-Wen Lou; Jia-Horng Lin; Jiwei Li (Chemical Engineering Journal, 2023)

Coupling phytotoxicity and human health risk assessment to refine the soil quality standard for As in farmlands - Kai-Wei Juang; Li-Jia Chu; Chien-Hui Syu; Bo-Ching Chen (Environmental Science and Pollution Research, 2022)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Passive Cavitation Enhancement Mapping via an Ultrasound Dual-Mode phased array to monitor blood-brain barrier opening - Trung Nguyen Hoang; Hsiang-Ching Lin; Chih-Hong Tsai; Cheng-Kai Jan; Hao-Li Liu (Journal of Medical and Biological Engineering, 2022)

Long-term dietary restriction ameliorates ageing-related renal fibrosis in male mice by normalizing mitochondrial functions and autophagy - Chun-Hsien Chiang; Sin-Jin Li; Ting-Rui Zhang; Ching-Yi Chen (Biogerontology, 2022)

The Role of Pericytes in the Articular Environment—a Review - Stefano Negri; Zhao Li; Yiyun Wang; Masnsen Cherief; Qizhi Qin; Jiajia Xu; Mario Armando Gomez Salazar; Ginny Ching-Yun Hsu; Aaron W. James (Current Tissue Microenvironment Reports, 2022)

Stochastic analysis of the variability of groundwater flow fields in heterogeneous confined aquifers of variable thickness - Ching-Min Chang; Chuen-Fa Ni; We-Ci Li; Chi-Ping Lin; I-Hsian Lee (Stochastic Environmental Research and Risk Assessment, 2022)

Correction to: Gene Selection in a Single Cell Gene Space Based on D–S Evidence Theory - Zhaowen Li; Qinli Zhang; Pei Wang; Fang Liu; Yan Song; Ching-Feng Wen (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Gene Selection in a Single Cell Gene Space Based on D–S Evidence Theory - Zhaowen Li; Qinli Zhang; Pei Wang; Fang Liu; Yan Song; Ching-Feng Wen (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Geographic distance, sedimentation, and substrate shape cryptic crustose coralline algal assemblages in the world’s largest subtropical intertidal algal reef - Shing Hei Zhan; Ling Chen; Chen‐Pan Liao; Wun‐Ruei Chang; Cheng‐Chin Li; Guang‐You Tang; Ching‐Yu Liou; Wei‐Lung Wang; Shih‐Wei Wang; Shao‐Lun Liu (Molecular Ecology, 2022)
Algal reefs, concreted by crustose coralline algae (CCA), are the main biotic reefs in temperate waters but rare in the subtropics and tropics. The world's largest known intertidal algal reef in the subtropics is the Taoyuan Algal Reef (TAR) located in the northwestern coast of Taiwan. The biodiversity and ecology of the TAR are scarcely explored, and now the reef is imperiled by industrialization. Here, we document cryptic species of CCA in Taiwan, particularly the TAR, by sequencing the psb A genes of over 1800 specimens collected across Taiwan. We also examine the ecological background of the TAR by surveying its benthic composition and measuring its environmental parameters. Our data reveal that the TAR harbours a high diversity of cryptic CCA species (27 molecular operational taxonomic units, or mOTUs), many of which are potentially new to science (18 mOTUs) and/or endemic to the TAR (9 mOTUs). Comparing the CCA species inventory of the TAR with the rest of Taiwan shows that the TAR represents a unique hotspot of CCA taxa in the waters of Taiwan. Our analyses show that variation in the CCA assemblages in the TAR is associated with geographic distance, sedimentation, and substrate type (for example, reef vs. hermit crab shell), suggesting that dispersal limitation and contemporary environmental selection shape the CCA assemblages in the TAR. The data from this study can inform the monitoring of human impacts on the health of the TAR and contribute to our understanding of the ecological processes underlying algal reef development.

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Superiority of Adipose-derived CD34 + Cells over Adipose-derived Stem Cells in Promoting Ischemic Tissue Survival - Yan-Jun Liu; Tian-Yu Zhang; Poh-Ching Tan; Pei-Qi Zhang; Yun Xie; Qing-Feng Li; Shuang-Bai Zhou (Stem Cell Reviews and Reports, 2022)

RETRACTED ARTICLE: Assessing the impact of green fiscal policies and energy poverty on energy efficiency - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Tai Duc Tran; Li Li (Environmental Science and Pollution Research, 2022)

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

Evaluating green innovation and performance of financial development: mediating concerns of environmental regulation - Ching-Chi Hsu; Ngo Quang-Thanh; FengSheng Chien; Li Li; Muhammad Mohsin (Environmental Science and Pollution Research, 2021)

Enhanced β-carotene production by overexpressing the DID2 gene, a subunit of ESCRT complex, in engineered Yarrowia lipolytica - Fan Yang; Liang Liu; Shan Qiang; Ching Yuan Hu; Ying Li; Yong Hong Meng (Biotechnology Letters, 2021)

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

A Case Study of Whistle Detection and Localization for Humpback Dolphins in Taiwan - Ching-Tang Hung; Wei-Yen Chu; Wei-Lun Li; Yen-Hsiang Huang; Wei-Chun Hu; Chi-Fang Chen (Journal of Marine Science and Engineering, 2021)
In recent years, Taiwan’s government has focused on policies regarding offshore wind farming near the Indo-Pacific humpback dolphin habitat, where marine mammal observation is a critical consideration. The present research developed an algorithm called National Taiwan University Passive Acoustic Monitoring (NTU_PAM) to assist marine mammal observers (MMOs). The algorithm performs whistle detection processing and whistle localization. Whistle detection processing is based on image processing and whistle feature extraction; whistle localization is based on the time difference of arrival (TDOA) method. To test the whistle detection performance, we used the same data to compare NTU_PAM and the widely used software PAMGuard. To test whistle localization, we designed a real field experiment where a sound source projected simulated whistles, which were then recorded by several hydrophone stations. The data were analyzed to locate the moving path of the source. The results show that localization accuracy was higher when the sound source position was in the detection region composed of hydrophone stations. This paper provides a method for MMOs to conveniently observe the migration path and population dynamics of cetaceans without ecological disturbance.

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Unexpected meteotsunamis prior to Typhoon Wipha and Typhoon Neoguri - Li-Ching Lin; Chin H. Wu (Natural Hazards, 2021)

Clinical Efficacy of a New Robot-assisted Gait Training System for Acute Stroke Patients - Andy Chien; Fei-Chun Chang; Nai-Hsin Meng; Pei-Yu Yang; Ching Huang; Li-Wei Chou (Journal of Medical and Biological Engineering, 2021)
Purpose Robot-assisted gait rehabilitation has been proposed as a plausible supplementary rehabilitation strategy in stroke rehabilitation in the last decade. However, its exact benefit over traditional rehabilitation remain sparse and unclear. It is therefore the purpose of the current study to comparatively investigate the clinical benefits of the additional robot-assisted training in acute stroke patients compared to standard hospital rehabilitation alone. Methods Ninety acute stroke patients (< 3 month) were recruited. All participants received the standard hospital neurorehabilitation comprises 45–60 min sessions daily for 3 weeks. Sixty patients also received an additional 30 min of robot-assisted gait training with the HIWIN MRG-P100 gait training system after each of the standard neurorehabilitation session. Outcome measures included: 1. Berg Balance Scale (BBS); 2. Brunnstrom Stage; 3. Pittsburgh Sleep Quality Index and 4. Taiwanese Depression Questionnaire (TDQ) which were assessed pre-treatment and then after every five training sessions. Results Both groups demonstrated significant improvement pre- and post-treatment for the BBS (robotic group p = 0.023; control group p = 0.033) but no significant difference (p > 0.1) between the groups were found. However, the robotic training group had more participants demonstrating larger BBS points of improvement as well as greater Brunnstrom stage of improvement, when compared to the control group. No significant within and between group statistical differences (p > 0.3) were found for Pittsburgh Sleep Quality Index and Taiwanese Depression Questionnaire. Conclusion The addition of robotic gait training on top of standard hospital neurorehabilitation for acute stroke patients appear to produce a slightly greater improvement in clinical functional outcomes, which is not transferred to psychological status.

Timing of coseismic displacement grid model construction for updating the semi-kinematic reference frame: case study in Taiwan - Shih-Han Hsiao; Kuo-En Ching; Kwo-Hwa Chen; Chien-Kuan Li (Journal of Geodesy, 2021)

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Temperature variation at the low‐latitude regions of East Asia recorded by tree rings during the past six centuries - Yu Liu; Ching‐Yao Li; Changfeng Sun; Huiming Song; Qiang Li; Qiufang Cai; Ruoshi Liu (International Journal of Climatology, 2020)
The understanding of past millennium climate change is very important. Due to the lack of continuously annual resolution records, the temperature characteristics in the low‐latitude regions of East Asia (LLREA) during past several centuries are still unknown. Using tree‐ring width chronology from Taiwan, an island located in the western Pacific region and in southeastern China, February–October mean temperature from 1380 to 2007 AD was reconstructed. Spatial correlation analysis indicated that the reconstructed temperature could represent the sea‐land temperature change in LLREA. During the past six centuries, both the warmest intervals and the largest variability of temperature appeared in the twentieth century. This is probably related to human activities. Temperature in LLREA provided good contrast with temperature changes in the Tibet Plateau and elsewhere in the Northern Hemisphere. The LLREA entered into the Little Ice Age around the year of 1450, approximately 100 years earlier than the Tibet Plateau. The 10‐year cycle contained in the reconstructed temperature is close to the 11‐year period of solar activity, which revealed there was a certain relationship between them. The temperature in LLREA significantly correlated with solar activity at the decadal to centennial scales. The strong/weak solar irradiance corresponded to the great/small temperature variability.

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Automatic Conformal Anti-radial Ultrasound Scanning for Whole Breast Screening - Ching-Yen Lee; Pai-Chi Li (Journal of Medical and Biological Engineering, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

The ongoing modernization of the Taiwan semi-dynamic datum based on the surface horizontal deformation model using GNSS data from 2000 to 2016 - Chien-Kuan Li; Kuo-En Ching; Kwo-Hwa Chen (Journal of Geodesy, 2019)

Extracting region-specific runout behavior and rainfall thresholds for massive landslides using seismic records: a case study in southern Taiwan - Ching Hung; Guan-Wei Lin; Ben Leshchinsky; Hsien-Li Kuo (Bulletin of Engineering Geology and the Environment, 2019)

Biophysically interpretable inference of single neuron dynamics - Vignesh Narayanan; Jr-Shin Li; ShiNung Ching (Journal of Computational Neuroscience, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Racial disparities in eligibility for low-dose computed tomography lung cancer screening among older adults with a history of smoking - Chien-Ching Li; Alicia K. Matthews; Mantle M. Rywant; Emily Hallgren; Raj C. Shah (Cancer Causes & Control, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Impulse Noise Denoising Using Confidence Measure with Non-sequential Process Order for X-Ray Bio-images - Ching-Ta Lu; Jun-Hong Shen; Ling-Ling Wang; Chih-Chan Hsu; Li-Ling Liu (Journal of Medical and Biological Engineering, 2018)

Racial variation in receipt of quality radiation therapy for prostate cancer - Daniel J. Lee; Zhiguo Zhao; Li-Ching Huang; Tatsuki Koyoma; Matthew J. Resnick; David F. Penson; Daniel A. Barocas; Karen E. Hoffman (Cancer Causes & Control, 2018)

Influence of Bacillus subtilis B068150 on cucumber rhizosphere microbial composition as a plant protective agent - Lihua Li; Jincai Ma; A. Mark Ibekwe; Qi Wang; Ching-Hong Yang (Plant and Soil, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Pressure-dependent Raman spectra of Ba5(PO4)3Cl alforsite - Shuangmeng Zhai; Zeming Li; Sean R. Shieh; Ching-Pao Wang; Weihong Xue (Physics and Chemistry of Minerals, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Optimization of the culture medium for recombinant protein production under the control of the αAmy3 promoter in a rice suspension-cultured cell expression system - Yu-Kuo Liu; Chia-Wei Lu; Jer-Yuan Chang; Ching-Fan Lu; Chia-Chun Tan; Li-Fen Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Automated Conformal Ultrasound Scanning for Breast Screening - Ching-Yen Lee; Tan-Loc Truong; Pai-Chi Li (Journal of Medical and Biological Engineering, 2018)

An Optimization Study for the Bone-Implant Interface Performance of Lumbar Vertebral Body Cages Using a Neurogenetic Algorithm and Verification Experiment - Chian-Her Lee; Ching-Chi Hsu; Li Chaing (Journal of Medical and Biological Engineering, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Assessing climate change adaptations for community-scale water resources using a low-frequency weather generator - Yuan-Hua Li; Ching-Pin Tung; Yuan-Hung Li; Pei-Yuan Chen (Paddy and Water Environment, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Effects of Carpal Tunnel Syndrome on Force Coordination and Muscle Coherence during Precision Pinch - Szu-Ching Lu; Kaihua Xiu; Ke Li; Tamara L. Marquardt; Peter J. Evans; Zong-Ming Li (Journal of Medical and Biological Engineering, 2017)

Anti-oxidative Responses on Hepatic Tissue of Zebrafish (Danio rerio) in a Short Duration of Sub-lethal Concentrations of Cadmium Exposure - Su Mei Wu; Li-Hsin Shu; Jia-Hao Liu; Ching Hsein Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Development of a novel engineered antibody targeting Neisseria species - Chih-Yueh Liu; Chang-Ching Weng; Chih-Hsiang Lin; Chiou-Ying Yang; Kwok-Kong Tony Mong; Yaw-Kuen Li (Biotechnology Letters, 2017)

Strain distribution, growth eccentricity, and tension wood distribution in the plagiotropic and orthotropic branches of Koelreuteria henryi Dummer - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Identification of microRNAs, phasiRNAs and Their Targets in Pineapple - Yun Zheng; Ting Li; Zhenning Xu; Ching Man Wai; Kun Chen; Xiaotuo Zhang; Shengpeng Wang; Bo Ji; Ray Ming; Ramanjulu Sunkar (Tropical Plant Biology, 2016)

A Smartphone Application Supporting Recovery from Heroin Addiction: Perspectives of Patients and Providers in China, Taiwan, and the USA - Marya Schulte; Di Liang; Fei Wu; Yu-Ching Lan; Wening Tsay; Jiang Du; Min Zhao; Xu Li; Yih -Ing Hser (Journal of Neuroimmune Pharmacology, 2016)

Study of tension wood in the artificially inclined seedlings of Koelreuteria henryi Dummer and its biomechanical function of negative gravitropism - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Poly(lactic-co-glycolide) polymer constructs cross-linked with human BMP-6 and VEGF protein significantly enhance rat mandible defect repair - Anusuya Das; Brian A. Fishero; J. Jared Christophel; Ching-Ju Li; Nikita Kohli; Yong Lin; Abhijit S. Dighe; Quanjun Cui (Cell and Tissue Research, 2016)

Monsoonal and lunar variability in microzooplankton abundance and community structure in the Terusan mangrove creek (Malaysia) - Yu Lin Yong; Li Lee Chew; Choon Weng Lee; Ving Ching Chong (Marine Biology Research, 2016)

Sensory determinants of valve rhythm dynamics provide in situ biodetection of copper in aquatic environments - Li-John Jou; Bo-Ching Chen; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Combined effect of rice genotypes and soil characteristics on iron plaque formation related to Pb uptake by rice in paddy soils - Fang-Lin Li; Ching-Ming Yang; Chien-Hui Syu; Dar-Yuan Lee; Ben-Jei Tsuang; Kai-Wei Juang (Journal of Soils and Sediments, 2016)

Spatial optimization procedure for land-use arrangement in a community based on a human comfort perspective - Pei-Yuan Chen; Ching-Pin Tung; Wei-Chih Lin; Yuan-Hua Li (Paddy and Water Environment, 2016)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Diversity and functional characterization of bacterial endophytes dwelling in various rice (Oryza sativa L.) tissues, and their seed-borne dissemination into rhizosphere under gnotobiotic P-stress - Asif Hameed; Meng-Wei Yeh; Yu-Ting Hsieh; Wei-Ching Chung; Chaur-Tsuen Lo; Li-Sen Young (Plant and Soil, 2015)

A single-repeat MYB transcription repressor, MYBH, participates in regulation of leaf senescence in Arabidopsis - Chun-Kai Huang; Pei-Ching Lo; Li-Fen Huang; Shaw-Jye Wu; Ching-Hui Yeh; Chung-An Lu (Plant Molecular Biology, 2015)

BK Induces cPLA2 Expression via an Autocrine Loop Involving COX-2-Derived PGE2 in Rat Brain Astrocytes - Chih-Chung Lin; Hsi-Lung Hsieh; Shiau-Wen Liu; Hui-Ching Tseng; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Integrated water resources system dynamics modeling and indicators for sustainable rural community - Yuan-Hua Li; Pei-Yuan Chen; Wei-Hsuan Lo; Ching-Pin Tung (Paddy and Water Environment, 2015)

TM4SF1: a new vascular therapeutic target in cancer - Chi-Iou Lin; Anne Merley; Tracey E. Sciuto; Dan Li; Ann M. Dvorak; Juan M. Melero-Martin; Harold F. Dvorak; Shou-Ching S. Jaminet (Angiogenesis, 2014)

Urinary metabolites of di(2-ethylhexyl) phthalate relation to sperm motility, reactive oxygen species generation, and apoptosis in polyvinyl chloride workers - Li-Ping Huang; Ching-Chang Lee; Jer-Pei Fan; Po-Hsiu Kuo; Tung-Sheng Shih; Ping-Chi Hsu (International Archives of Occupational and Environmental Health, 2014)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Impact of the exopolysaccharides Pel and Psl on the initial adhesion of Pseudomonas aeruginosa to sand - Lulu Tian; Shangping Xu; William C. Hutchins; Ching-Hong Yang; Jin Li (Biofouling, 2014)

Impact of Different Vehicles for Laser-Assisted Drug Permeation via Skin: Full-Surface versus Fractional Ablation - Woan-Ruoh Lee; Shing-Chuan Shen; Ibrahim A. Aljuffali; Yi-Ching Li; Jia-You Fang (Pharmaceutical Research, 2014)

Quartet Analysis of Putative Horizontal Gene Transfer in Crenarchaeota - Travers H. Ching; Brandon A. Yoza; Qing X. Li (Journal of Molecular Evolution, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Human white adipose tissue vasculature contains endothelial colony-forming cells with robust in vivo vasculogenic potential - Ruei-Zeng Lin; Rafael Moreno-Luna; Rocio Muñoz-Hernandez; Dan Li; Shou-Ching S. Jaminet; Arin K. Greene; Juan M. Melero-Martin (Angiogenesis, 2013)

Better environmental data may reverse conclusions about niche‐ and dispersal‐based processes in community assembly - Li-Wan Chang; David Zelený; Ching-Feng Li; Shau-Ting Chiu; Chang-Fu Hsieh (Ecology, 2013)
Variation partitioning of species composition into components explained by environmental and spatial variables is often used to identify a signature of niche‐ and dispersal‐based processes in community assembly. Such interpretation, however, strongly depends on the quality of the environmental data available. In recent studies conducted in forest dynamics plots, the environment was represented only by readily available topographical variables. Using data from a subtropical broad‐leaved dynamics plot in Taiwan, we focus on the question of how would the conclusion about importance of niche‐ and dispersal‐based processes change if soil variables are also included in the analysis. To gain further insight, we introduced multiscale decomposition of a pure spatial component [c] in variation partitioning. Our results indicate that, if only topography is included, dispersal‐based processes prevail, while including soil variables reverses this conclusion in favor of niche‐based processes. Multiscale decomposition of [c] shows that if only topography was included, broad‐scaled spatial variation prevails in [c], indicating that other as yet unmeasured environmental variables can be important. However, after also including soil variables this pattern disappears, increasing importance of meso‐ and fine‐scaled spatial patterns indicative of dispersal processes.

Mechanism of Two Novel Human GJC3 Missense Mutations in Causing Non-Syndromic Hearing Loss - Ching-Chyuan Su; Shuan-Yow Li; Yung-Chang Yen; Jhih-Hao Nian; Wei-Guang Liang; Jiann-Jou Yang (Cell Biochemistry and Biophysics, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

Skin Permeation of Small-Molecule Drugs, Macromolecules, and Nanoparticles Mediated by a Fractional Carbon Dioxide Laser: The Role of Hair Follicles - Woan-Ruoh Lee; Shing-Chuan Shen; Saleh A. Al-Suwayeh; Hung-Hsu Yang; Yi-Ching Li; Jia-You Fang (Pharmaceutical Research, 2013)

Cordyceps sinensis protects against renal ischemia/reperfusion injury in rats - Hua-Pin Wang; Ching-Wen Liu; Hsueh-Wen Chang; Jen-Wei Tsai; Ya-Zhu Sung; Li-Ching Chang (Molecular Biology Reports, 2013)

Candida sanyaensis sp. nov., an ascomycetous yeast species isolated from soil - Feng-Li Hui; Qiu-Hong Niu; Tao Ke; Ying-Xia Li; Ching-Fu Lee (Antonie van Leeuwenhoek, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

A transposable element insertion within ZmGE2 gene is associated with increase in embryo to endosperm ratio in maize - Pan Zhang; William B. Allen; Nobuhiro Nagasawa; Ada S. Ching; Elmer P. Heppard; Hui Li; Xiaomin Hao; Xiaowei Li; Xiaohong Yang; Jianbing Yan; Yasuo Nagato; Hajime Sakai; et al. (Theoretical and Applied Genetics, 2012)

Biomechanical features of eccentric cambial growth and reaction wood formation in broadleaf tree branches - Ching-Chu Tsai; Li-Fen Hung; Ching-Te Chien; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2012)

Influence of weather conditions on hiking behavior - Ching Li; Shu-Hua Lin (International Journal of Biometeorology, 2012)

Phylodynamics of H5N1 avian influenza virus in Indonesia - TOMMY TSAN‐YUK LAM; CHUNG‐CHAU HON; PHILIPPE LEMEY; OLIVER G. PYBUS; MANG SHI; HEIN MIN TUN; JUN LI; JINGWEI JIANG; EDWARD C. HOLMES; FREDERICK CHI‐CHING LEUNG (Molecular Ecology, 2012)
Understanding how pathogens invade and become established in novel host populations is central to the ecology and evolution of infectious disease. Influenza viruses provide unique opportunities to study these processes in nature because of their rapid evolution, extensive surveillance, large data sets and propensity to jump species boundaries. H5N1 highly pathogenic avian influenza virus (HPAIV) is a major animal pathogen and public health threat. The virus is of particular importance in Indonesia, causing severe outbreaks among poultry and sporadic human infections since 2003. However, little is known about how H5N1 HPAIV emerged and established in Indonesia. To address these questions, we analysed Indonesian H5N1 HPAIV gene sequences isolated during 2003–2007. We find that the virus originated from a single introduction into East Java between November 2002 and October 2003. This invasion was characterized by an initially rapid burst of viral genetic diversity followed by a steady rate of lineage replacement and the maintenance of genetic diversity. Several antigenic sites in the haemagglutinin gene were subject to positive selection during the early phase, suggesting that host‐immune‐driven selection played a role in host adaptation and expansion. Phylogeographic analyses show that after the initial invasion of H5N1, genetic variants moved both eastwards and westwards across Java, possibly involving long‐distance transportation by humans. The phylodynamics we uncover share similarities with other recently studied viral invasions, thereby shedding light on the ecological and evolutionary processes that determine disease emergence in a new geographical region.

The species richness–productivity relationship in the herb layer of European deciduous forests - Irena Axmanová; Milan Chytrý; David Zelený; Ching‐Feng Li; Marie Vymazalová; Jiří Danihelka; Michal Horsák; Martin Kočí; Svatava Kubešová; Zdeňka Lososová; Zdenka Otýpková; Lubomír Tichý; et al. (Global Ecology and Biogeography, 2012)
Aim In contrast to non‐forest vegetation, the species richness–productivity (SR‐P) relationship in forests still remains insufficiently explored. Several studies have focused on the diversity of the tree layer, but the species richness of temperate deciduous forests is mainly determined by their species‐rich herb layer. The factors controlling herb‐layer productivity may differ from those affecting tree layers or open herbaceous vegetation, and thus the SR‐P relationship and its underlying processes may differ. However, the few relevant studies have reported controversial results. Here we explore the SR‐P relationship in the forest herb layer across different areas from oceanic to continental Europe, and put the effect of habitat productivity on species richness into context with other key factors, namely soil pH and light availability. Location North‐western Germany, Czech Republic, Slovakia and southern Urals (Russia). Methods We measured herb‐layer species richness and biomass, soil pH and tree‐layer cover in 156 vegetation plots of 100 m 2 in deciduous forests. We analysed the SR‐P relationship and the relative importance of environmental variables using regression models for particular areas and separate forest types. Results We found a consistent monotonic increase in the herb‐layer species richness with productivity across all study areas and all forest types. Soil pH and light availability also affected species richness, but their relative importance differed among areas. Main conclusions We suggest that the monotonically increasing SR‐P relationship in the forest herb layer results from the fact that herb‐layer productivity is limited by canopy shading; competition within the herb layer is therefore not strong enough to exclude many species. This differs fundamentally from open herbaceous vegetation, which is not subject to such productivity limits and consequently exhibits a unimodal SR‐P relationship. We present a conceptual model that might explain the differences in the SR‐P relationship between the forest herb layer and open herbaceous vegetation.

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Differential neuronal changes in medial prefrontal cortex, basolateral amygdala and nucleus accumbens after postweaning social isolation - Yu-Chun Wang; Ue-Cheung Ho; Meng-Ching Ko; Chun-Chieh Liao; Li-Jen Lee (Brain Structure and Function, 2012)

Toxicokinetics/toxicodynamics with damage feedback improves risk assessment for tilapia and freshwater clam exposed to arsenic - Wei-Yu Chen; Chung-Min Liao; Yun-Ru Ju; Sher Singh; Li-John Jou; Bo-Ching Chen; Jeng-Wei Tsai (Ecotoxicology, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Down-Regulation of Tumor-Associated NADH Oxidase, tNOX (ENOX2), Enhances Capsaicin-Induced Inhibition of Gastric Cancer Cell Growth - His-Ming Wang; Show-Mei Chuang; Yu-Ching Su; Yi-Hui Li; Pin Ju Chueh (Cell Biochemistry and Biophysics, 2011)

Association of gene polymorphisms in prolactin and its receptor with breast cancer risk in Taiwanese women - Fan-Yun Mong; Yu-Liang Kuo; Ching-Wen Liu; Wen-Sheng Liu; Li-Ching Chang (Molecular Biology Reports, 2011)

Identification of QTL genes for BMD variation using both linkage and gene-based association approaches - Gloria Hoi-Yee Li; Ching-Lung Cheung; Su-Mei Xiao; Kam-Shing Lau; Yi Gao; Cora H. Bow; Qing-Yang Huang; Pak-Chung Sham; Annie Wai-Chee Kung (Human Genetics, 2011)

Activation of regulatory T cells instigates functional down-regulation of cytotoxic T lymphocytes in human breast cancer - Chao-Hsu Li; Wen-Hong Kuo; Wen-Chun Chang; Su-Cheng Huang; King-Jen Chang; Bor-Ching Sheu (Immunologic Research, 2011)

Human Connexin30.2/31.3 (GJC3) does not Form Functional Gap Junction Channels but Causes Enhanced ATP Release in HeLa Cells - Wei-Guang Liang; Ching-Chyuan Su; Jhih-Hao Nian; Ann-Shyn Chiang; Shuan-Yow Li; Jiann-Jou Yang (Cell Biochemistry and Biophysics, 2011)

TM4SF1: a tetraspanin-like protein necessary for nanopodia formation and endothelial cell migration - Andrew Zukauskas; Anne Merley; Dan Li; Lay-Hong Ang; Tracey E. Sciuto; Samantha Salman; Ann M. Dvorak; Harold F. Dvorak; Shou-Ching Shih Jaminet (Angiogenesis, 2011)

Prostaglandin I2 analogues suppress TNF-α expression in human monocytes via mitogen-activated protein kinase pathway - Wei-Li Wang; Chang-Hung Kuo; Yu-Te Chu; Ching-Hua Huang; Ka-Pan Lam; Shau-Ku Huang; Yuh-Jyh Jong; Yu-Ting Kuo; Chih-Hsing Hung (Inflammation Research, 2011)

Environmental factors influencing herb layer productivity in Central European oak forests: insights from soil and biomass analyses and a phytometer experiment - Irena Axmanová; David Zelený; Ching-Feng Li; Milan Chytrý (Plant and Soil, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Asterotremella meifongana sp. nov. and Asterotremella nantouana sp. nov., two anamorphic basidiomycetous yeasts isolated from soil and mushrooms - Yi-Ru Liu; Li-Ying Huang; Suh-Shen Young; Chin-Feng Chang; Ching-Fu Lee (Antonie van Leeuwenhoek, 2011)

Saturnispora serradocipensis sp. nov. and Saturnispora gosingensis sp. nov., two ascomycetous yeasts from ephemeral habitats - Monica R. Canelhas; Anne C. Barbosa; Adriana O. Medeiros; Ching-Fu Lee; Li-Yin Huang; Marc-André Lachance; Carlos A. Rosa (Antonie van Leeuwenhoek, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

5,5-Diphenyl-2-thiohydantoin-N10 (DPTH-N10) suppresses proliferation of cultured colon cancer cell line COLO-205 by inhibiting DNA synthesis and activating apoptosis - Tong-Sheng Lee; Li-Ching Chen; Yuan Liu; Jender Wu; Yu-Chih Liang; Wen-Sen Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Editing of accD and ndhF chloroplast transcripts is partially affected in the Arabidopsis vanilla cream1 mutant - Ching-Chih Tseng; Tzu-Ying Sung; Yi-Chiou Li; Shih-Jui Hsu; Chien-Li Lin; Ming-Hsiun Hsieh (Plant Molecular Biology, 2010)

Subcellular localization of Mitf in monocytic cells - Ssu-Yi Lu; Hsiao-Ching Wan; Mengtao Li; Yi-Ling Lin (Histochemistry and Cell Biology, 2010)

Erratum to: Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Lin; Shuan-Yow Li (Human Genetics, 2010)

Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Li; Shuan-Yow Li (Human Genetics, 2010)

A Mediated Glucose Biosensor Incorporated with Reverse Iontophoresis Function for Noninvasive Glucose Monitoring - Congo Tak-Shing Ching; Tai-Ping Sun; Su-Hua Huang; Hsiu-Li Shieh; Chung-Yuan Chen (Annals of Biomedical Engineering, 2010)

A novel mutation in the connexin 29 gene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Ching-Chyuan Su; Juan-Yu Chang; Tung-Cheng Li; Shuan-Yow Li (Human Genetics, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Interval number fuzzy linear programming for climate change impact assessments of reservoir active storage - Ching-Pin Tung; Nien-Ming Hong; Ming-hsu Li (Paddy and Water Environment, 2009)

Assessing the impact of climate change on the land hydrology in Taiwan - Ming-Hsu Li; Waiting Tien; Ching-Pin Tung (Paddy and Water Environment, 2009)

Complex genomic organization of Indian muntjac centromeric DNA - Ya-Ming Cheng; Tzai-Shiuan Li; Lie-Jiau Hsieh; Pei-Ching Hsu; Yueh-Chun Li; Chyi-Chyang Lin (Chromosome Research, 2009)

Ameliorative effects of Vaccaria segetalis extract on osteopenia in ovariectomized rats - Chun-Ching Shih; Cheng-Hsiu Lin; Wei-Li Lin (Journal of Natural Medicines, 2009)

Allocating the costs of multi-purpose water resource development: a case study of Chi-Chi Weir in Taiwan - Li-Chun Huang; Ching-Kai Hsiao; Sheng-Feng Kuo (Paddy and Water Environment, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Alnus acuminata in dual symbiosis withFrankia and two different ectomycorrhizal fungi (Alpova austroalnicola andAlpova diplophloeus) growing in soilless growth medium - Alejandra G. Becerra; Eugenia Menoyo; Irene Lett; Ching Y. Li (Symbiosis, 2009)

Ventral coloration differentiation and mitochondrial sequences of the Chinese Cobra (Naja atra) in Taiwan - Hua-Ching Lin; Shou-Hsien Li; Jonathan Fong; Si-Min Lin (Conservation Genetics, 2008)

Expression and localization of Tmie in adult rat cochlea - Mao-Chang Su; Jiann-Jou Yang; Ming-Yung Chou; Chung-Han Hsin; Ching-Chyuan Su; Shuan-Yow Li (Histochemistry and Cell Biology, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Changes in hydrogeological properties of the River Choushui alluvial fan aquifer due to the 1999 Chi-Chi earthquake, Taiwan - Cheng-Shin Jang; Chen-Wuing Liu; Yeeping Chia; Li-Hsin Cheng; You-Ching Chen (Hydrogeology Journal, 2008)

Isolation and characterization of the zebrafish Danio rerio insulin-like growth factor binding protein-3 promoter region - Ming Jun CHOU; Jian Chyi CHEN; Jyh Yih CHEN; Hong Yi GONG; Li Tzu LI; Tzou Chi HUANG; Jen Leih WU; Ching Ming KUO (Fisheries Science, 2008)

The blood-brain barrier in the cerebrum is the initial site for the Japanese encephalitis virus entering the central nervous system - Tsan-Hsiun Liu; Li-Ching Liang; Chien-Chih Wang; Huei-Chung Liu; Wei-June Chen (Journal of NeuroVirology, 2008)

Lignans and anthraquinones from the fruits of Morinda citrifolia - Chwan Fwu Lin; Ching Li Ni; Yu Ling Huang; Shuenn Jyi Sheu; Chien Chih Chen (Natural Product Research, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Fine mapping of the Pc locus of Sorghum bicolor, a gene controlling the reaction to a fungal pathogen and its host-selective toxin - Ervin D. Nagy; Tso-Ching Lee; Wusirika Ramakrishna; Zijun Xu; Patricia E. Klein; Phillip SanMiguel; Chiu-Ping Cheng; Jingling Li; Katrien M. Devos; Keith Schertz; Larry Dunkle; Jeffrey L. Bennetzen (Theoretical and Applied Genetics, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Polyacetylenes Function as Anti-Angiogenic Agents - Li-Wha Wu; Yi-Ming Chiang; Hsiao-Ching Chuang; Sheng-Yang Wang; Ga-Wen Yang; Ya-Huey Chen; Ling-Ya Lai; Lie-Fen Shyur (Pharmaceutical Research, 2004)

Distribution and sub-cellular localization of the aflatoxin enzyme versicolorin B synthase in time-fractionated colonies of Aspergillus parasiticus - Ching-Hsun Chiou; Li-Wei Lee; Shirley A. Owens; Joanne H. Whallon; Karen L. Klomparens; Craig A. Townsend; John E. Linz (Archives of Microbiology, 2004)

Subcellular localization of aflatoxin biosynthetic enzymes Nor-1, Ver-1, and OmtA in time-dependent fractionated colonies of Aspergillus parasiticus - Li-Wei Lee; Ching-Hsun Chiou; Karen L. Klomparens; Jeffrey W. Cary; John E. Linz (Archives of Microbiology, 2004)

Alpha-naphthoflavone induces vasorelaxation through the induction of extracellular calcium influx and NO formation in endothelium - Yu-Wen Cheng; Ching-Hao Li; Chen-Chen Lee; Jaw-Jou Kang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Tripartite associations in an alder: effects of Frankia and Alpova diplophloeus on the growth, nitrogen fixation and mineral acquisition of Alnus tenuifolia - Takashi Yamanaka; Ching-Y. Li; Bernard T. Bormann; Hiroaki Okabe (Plant and Soil, 2003)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)

Characterization of an IS Element in Mycoplasma orale That Is Highly Homologous to M. fermentans ISLE - Susan E. Ditty; BingJie Li; Shimin Zhang; Nianxiang Zou; Shyh-Ching Lo (Current Microbiology, 2003)

Increased acidification in the rhizosphere of cactus seedlings induced by Azospirillum brasilense - Angel Carrillo; Ching Li; Yoav Bashan (The Science of Nature, 2002)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

Cloning and characterization of a DEAD box RNA helicase from the viable seedlings of aged mung bean - Sing-Chung Li; Mei-Chu Chung; Ching-San Chen (Plant Molecular Biology, 2001)

Distinct regulation of genes by bFGF and VEGF-A in endothelial cells - Yng-Jyh Jih; Wen-Hui Lien; Wen-Chi Tsai; Ga-Wen Yang; Ching Li; Li-Wha Wu (Angiogenesis, 2001)

Rodent malarias: the mouse as a model for understanding immune responses and pathology induced by the erythrocytic stages of the parasite - Ching Li; Elsa Seixas; Jean Langhorne (Medical Microbiology and Immunology, 2001)

Developing an improved In vitro propagation system for slow-growing species using garcinia mangostana L. (mangosteen) - Li-Chun Huang; Bau-Liang Huang; Chiu Hui Wang; Ching-I Kuo; Toshio Murashige (In Vitro Cellular & Developmental Biology - Plant, 2000)

Relationship between ammonium accumulation and senescence of detached rice leaves caused by excess copper - Li-Men Chen; Ching Huei Kao (Plant and Soil, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

A case-control study of diet and colorectal cancer in a multiethnic population in Hawaii (United States): lipids and foods of animal origin - Loïc Le Marchand; Lynne R. Wilkens; Jean H. Hankin; Laurence N. Kolonel; Li-Ching Lyu (Cancer Causes & Control, 1997)

Effect of the peroxisome proliferator perfluorodecanoic acid on growth and lipid metabolism in Sprague Dawley rats fed three dietary levels of selenium - Tim Borges; Howard P. Glauert; Li -Chuan Chen; Ching K. Chow; Larry W. Robertson (Archives of Toxicology, 1990)

Effects of torula and brewer's yeast diets in obese and lean mice - B. J. Stoecker; Yi-Ching Li; D. B. Wester; Sau-Bin Chan (Biological Trace Element Research, 1987)